Agritourism As a Tool for Sustainable Local Development: The Case of Thuy Bieu, Vietnam - Trinh, Thi Thu Thao (Auckland University of Technology, 2021)
Agritourism has proved to be a viable diversification strategy for farmers to enhance their quality of life and, prior to COVID-19, had gained ground in terms of not only visitor numbers and demand but also attention from practitioners and policymakers. Despite such growth, not much attention has been paid to the range of elements that comprise the agritourism network and its impacts on local development as perceived by host communities. This doctoral research addressed this gap by conducting a case study focused on Thuy Bieu village, an area well known for agritourism practices based on its iconic pomelo. To advance the understanding of agritourism in terms of its stakeholder network and its impacts on the local community, this research adopted a subjective epistemology viewing knowledge as socially constructed through language and interaction, and a qualitative approach using interviews, observation and social network analysis techniques. A conceptual framework encompassing three key elements (the agritourism system, its related impacts, and host perceptions) underpins the research, along with network-related theories (stakeholder and network theory) and perception-related approaches (social exchange and social representation theory). The qualitative approach used here represents a departure from the quantitative methods which tend to dominate other research studies in the field. The findings show that the agritourism system of Thuy Bieu comprises a wide range of agritourism stakeholders connected to each other through various interactions that revolve around the exchange of diverse resources. The thesis also reveals varying degrees of local people’s involvement in tourism practice which, in turn, influences their perception of the impact agritourism has on community development and, accordingly, their responses to the phenomenon. The thesis adds distinctive theoretical and methodological contributions to the growing body of literature on agritourism and its links to sustainable local development. The study achieves its objectives of: (1) developing the agritourism system model encompassing key stakeholders and their interrelationships at a local scale, (2) conceptualising agritourism as a tool for sustainable local development and, (3) advancing the incipient understanding of this phenomenon in Vietnam. The thesis will benefit local authority and agritourism practitioners by providing empirical evidence upon which to base policies and strategies that facilitate desired development outcomes. With a strong focus on sustainability and a detailed understanding of local community perspectives, the thesis reinforces the recognition of agritourism as a tool for sustainable development worldwide. This thesis encourages the implementation and development of agritourism in more communities, especially those in developing countries aiming for sustainable development.
Keywords: Agritourism; Vietnam; Stakeholder network; SNA; Agritourism impacts; Local development; Local community; Host perception; Sustainability